Effect of Sirolimus on the Level of Peripheral Blood Lymphocyte Autophagy in Children With Systemic Lupus Erythematosus - Wang, Xinliang; Su, Qingxiao; Dou, Zhiyan; Zhao, Xue; Zhang, Naiqi; Yu, Bo; Wang, Yuxue; Rong, Zanhua (Frontiers in Pediatrics, 2021)
Background: To observe the changes of autophagy-related protein levels in peripheral blood lymphocytes before and after sirolimus treatment in children with systemic lupus erythematosus (SLE). Methods: Children with SLE were randomly divided into two groups, 28 in the traditional treatment group and 28 in the sirolimus group. Fifteen healthy children who were in the same period were collected as the normal control group. Clinical laboratory indexes, the percentage of routine lymphocytes, complement C3, complement C4, serum Anti-dsDNA and SLEDAI were detected. Results: At 3 and 6 months after treatment, compared with the traditional treatment group, the percentage of routine lymphocytes in the sirolimus group increased (P=0.03), SLEDAI score and positive rate of Anti-dsDNA decreased (P=0.01). Compared with normal children, the expression of microtubule‐associated protein 1 light chain 3 (LC3) protein in peripheral blood lymphocytes was significantly higher (P=0.006); peripheral blood expression of P62/SQSTM1 (sequestosome 1) protein in lymphocytes decreased (P=0.02). Conclusion: Sirolimus can play a role in the treatment of systemic lupus erythematosus by regulating the level of autophagy.